Simple and Visible Detection of Novel Astroviruses Causing Fatal Gout in Goslings Using One-Step Reverse Transcription Polymerase Spiral Reaction Method - Ji, Jun; Chen, Qinxi; Yu, Zhengli; Xu, Xin; Mu, Xinhao; Tian, Xiang; Fu, Xiaoge; Yao, Lunguang; Bi, Yingzuo; Xie, Qingmei (Frontiers in Veterinary Science, 2020)
In this study, a one-step isothermal method combining polymerase spiral reaction (PSR) with reverse transcription (RT-PSR) was established for rapid and specific detection of novel astroviruses causing fatal gout in goslings (N-GoAstV). The one-step RT-PSR was accomplished at the optimal temperature of 62°C and time of 40 min and used primers simply designed as conventional PCR primers, and the results of detection were visible to the naked eye. The detection limit of PSR was above 34.7 copies /µL at a 95% probability level according to probit regression analysis. The assay specifically detected N-GoAstV and no other reference viruses were detected. These results suggest that the newly established RT-PSR assay could one-step accomplish reverse-transcription, amplification, and result determination providing a visible, convenient, rapid, and cost-effective test that can be carried out onsite, in order to ensure timely quarantine of N-GoAstV-infected birds, leading to effective disease control.